Impact of complexity and experience on energy investment decisions for residential buildings - Benedikt Maciosek; Mehdi Farsi; Sylvain Weber; Martin Jakob (University of Neuchâtel, Institute of Economic Research (IRENE), 2022)
Complexity within the decision-making process can inhibit energy investment for residential buildings. In this paper, we explore effects of complexity on investment behaviour, as well as the impact of experience with similar investments and of subsidies as a promoting policy tool. To shed light on these issues, we conduct a discrete choice experiment (DCE) among homeowners. Furthermore, we investigate appreciation of a simplifying one-stop-shop concept and calculate the willingness to invest. Our results show that homeowners are interested in energy investments and have a positive but decreasing marginal willingness to invest. Subsidies matter for investment choices, and their effect more than offsets the negative impact of costs. Experience with similar investments plays a role for single homeowners and especially those who are familiar with subsidies seem to be interested in the onestop-shop concept.
Keywords: D12; L94; Q41; 330; Energy efficiency; Renewable energy; Discrete choice experiment; Conditional logit models